Study on Industrial FMS (Flexible Manufacturing System) Communication - Mohd. Mohsin Khan, Dr. Kishan Pal Singh, Dr. Wasif Ullah Khan (International Journal of Advanced Science and Technology, 2020)
Flexible manufacturing system is an integrated manufacturing system of computer-controlled machine tools, transportation and handling systems under the control of a larger computer. Flexibility is attained by having an overall system of control that directs the functions of both the computer-controlled machine tools and the handling systems. These computer systems are designed to be programmed or grouped easily with other devices to be able to allow fast and economical changes in manufacturing process, enabling quick responses to the market changes and allowing mass customization of products. The purpose of this paper is to perform a contrast study on Industrial FMS( Flexible Manufacturing System) being in use in apparel and manufacturing Industries. Here we will study the significant differences in the technologies. Detailed discussions  on advantages and disadvantages of this technology, comparable contributions of FMS at various dimensions. Recommendation for future research are also provided.